Assessment of Coral Reef Condition and Management Strategy in the Biak Timur Watershed, Biak Numfor - Selfinus Pattiasina; Fatmawati Marasabessy (Agrikan: Jurnal Agribisnis Perikanan, 2020)
This study aims to assess the condition of the coral reef ecosystem in East Biak waters and formulate a strategy for optimal and sustainable management of coral reef ecosystems in the waters of East Biak, Biak Numfor Regency. Data and information were collected through the application of various methods, namely field surveys using transect techniques, interviews using questionnaires and document tracing. The data analysis method consisted of analyzing the condition of the coral reef ecosystem, SWOT analysis. The results showed that the waters of East Biak had very varied coral reef ecosystem conditions with a range of 22 - 85% with an average percentage of coral cover of 68.78% and when compared to the percentage of coral cover in 2018 there was an increase of 12%, although found in some location has decreased. In the management of coral reef ecosystems in this area there is support from the government, but due to budget constraints, the management has not been carried out optimally. From the analysis, several management alternatives are recommended, namely; (1) Optimizing coral reef management through; zoning arrangements for coastal and marine areas, increasing community, private and government participation in coral reef management and strengthening regional regulations; (2) Conservation and rehabilitation of coral reef ecosystems through; strengthening regional marine conservation areas, carrying out conservation and rehabilitation of coral reef ecosystems, regulating fish utilization activities in the area, integrated law enforcement and strengthening community-based monitoring and supervision systems; and (3) Increasing the quality of life of the community through; public awareness of the importance of coral reefs, community empowerment, repositioning of community livelihoods and developing technology for the utilization of marine biological resources that are effective and environmentally friendly.